ANALISIS SPEECH DELAY PADA ANAK USIA 2 TAHUN (KAJIAN PSIKOLINGUISTIK) - Munjiah; Tantie Imeldha; Sundawati Tisnasari (Jurnal Bastra (Bahasa dan Sastra), 2026)
Language is a system of vocal symbols used by humans in the communication process in everyday life. Speaking is a verbal communication process, so that the interlocutor can more easily understand the meaning conveyed. Children can learn to speak in two ways: first, by imitating the models they see, either from peers or from older people. Second, with training provided by adults through specific guidance and direction. Speech delay or delayed speech in children is a condition where the child's ability to speak is below the normal development stage according to their age. Children with speech delays have not achieved the language skills that should have been mastered at their age. This study aims to analyze the factors that cause speech delay, anticipatory steps taken by parents, and the benefits of these anticipatory efforts. This study uses a qualitative descriptive method, with data collected through listening and recording techniques. The results of the study indicate that there are four main factors that cause speech delay in children, namely because of the gap between children and parents, language delays influenced by gender, lack of attention from parents, and lack of care and interaction with parents. The anticipation carried out by parents is by providing daycare training to children. The benefit is that now the child has developed in his speaking process.